Aboriginal-Social Justice Alliances: Understanding the Landscape of Relationships through the Coalition for a Public Inquiry into Ipperwash - Davis, Lynne; O'Donnell, Vivian; Shpuniarsky, Heather (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2007)
Despite their growing popularity, alliances and coalitions between Indigenous peoples and other actors fighting for social and environmental justice have been little documented or analyzed. Alliances form often in the context of land and resource disputes, struggles against discrimination and racism, and other areas of life where there are grounds for strategic co-operation. Using grounded theory and resource mobilization theory, this study examines relationships between social justice and Indigenous activists who formed the "Coalition for a Public Inquiry into Ipperwash", a social justice struggle in Ontario, Canada. The authors analyze participants' narratives noting their understandings of their relationships, strengths and tensions, and lessons learned. It is apparent that Indigenous and social movement alliances represent an exceptional site of encounter and transformation, always in the shadow of ongoing colonization and the movement to Indigenous self-determination. The Coalition provides a window into complex relationships that are forming across Canada and globally.